Kontrol Suhu Menggunakan Metode PI (Proportional-Integral) Untuk Proses Perebusan Pada Alat Pembuatan Jamu Kunyit Asam - Fauziyah, Mila; Adhisuwignjo, Supriatna; Febriyana, Anita Dwi (Program Studi Teknik Elektro Universitas Khairun, 2022)
Turmeric and tamarind herbal medicine is a traditional drink made from two different types of species, namely turmeric and tamarind. These two spices, but also processed into nutritious drinks. One of the benefits of this herbal medicine is to increase the body’s immunity. In the situation of the covid-19 pandemic, enthusiasts of the turmeric and tamarind herbal medicine are increasing, it is necessary to pay attention to the optimum quality of the product. The quality of the turmeric and tamarind herbal medicine can be seen from the boiling process. A good boiling process at a temperature of 60o-90oC to maintain the vitamin C content in turmeric, so it is necessary to control the temperature to maintain a stable boiling temperature. The control method used in this study is the PI control method to control the actuator in the form of a servo motor. In this manufacture, Arduino Uno is used as a microcontroller with DS18B20 input as a temperature sensor. By using the PI control method, the control parameters obtained by the Ziegler Nichols method with values of Kp= 12.2, Ki=0.04 and Kd=0. From the results of system testing on the PI controller application using the Ziegler Nichols method, the value (Tr) = 36 minutes, (Tp) = 31 minutes, (Ts) = 45 minutes, steady state = 0.2%, (Po) = 0, 41%